1999
DOI: 10.1002/(sici)1521-2254(199903/04)1:2<134::aid-jgm17>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

GlycofectionTM in the presence of anionic fusogenic peptides: a study of the parameters affecting the peptide-mediated enhancement of the transfection efficiency

Abstract: Gene delivery mediated by polyplexes such as DNA complexed with polylysine conjugates is limited by the low efficiency of escape of DNA from the endosomes. One of the strategies which favors the transmembrane passage of polyplexes consists of adding anionic amphipathic peptides capable of destabilizing membranes in an acidic medium. Although less efficient than replication‒defective adenoviruses, fusogenic peptides increase the expression of the reporter gene by a factor between 100 and 1000 depending on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…An anionic peptide E5CA, derived from this viral peptide, was shown to help the transfer of plasmids in various transfection assays [19], and to induce a rapid cell uptake of both F-psODN and fluorescein-labelled phosphodiester-type ODN upon transient acidification of the extracellular medium [15]. Dimeric peptides, obtained by linking the C-terminal amino acid to a simple stem peptide, were found to be more efficient than their monomers in transferring genes with plasmidic DNAglycosylated poly-lysine complexes [22] or DNA-poly-lysinetransferrin complexes [20,21]. Furthermore, Freulon et al [31] showed that the transfection efficiency of cells was higher in the presence of the dimer (E5WYGGAA) # KA (8i10& relative light units\10' cells) than in the presence of the corresponding monomer E5WYG (1.5i10& relative light units\10' cells) or in absence of any anionic peptide (3i10$ relative light units\10' cells), and found that the dimer efficiency was dependent on the length of the spacer which links the two monomeric stretches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An anionic peptide E5CA, derived from this viral peptide, was shown to help the transfer of plasmids in various transfection assays [19], and to induce a rapid cell uptake of both F-psODN and fluorescein-labelled phosphodiester-type ODN upon transient acidification of the extracellular medium [15]. Dimeric peptides, obtained by linking the C-terminal amino acid to a simple stem peptide, were found to be more efficient than their monomers in transferring genes with plasmidic DNAglycosylated poly-lysine complexes [22] or DNA-poly-lysinetransferrin complexes [20,21]. Furthermore, Freulon et al [31] showed that the transfection efficiency of cells was higher in the presence of the dimer (E5WYGGAA) # KA (8i10& relative light units\10' cells) than in the presence of the corresponding monomer E5WYG (1.5i10& relative light units\10' cells) or in absence of any anionic peptide (3i10$ relative light units\10' cells), and found that the dimer efficiency was dependent on the length of the spacer which links the two monomeric stretches.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal peptide of the influenza virus haemagglutinin subunit HA2 is known to adopt an amphipathic helical conformation and to destabilize lipid bilayers in an acidic environment. Based on this concept, synthetic derivatives have been proposed to deliver nucleic acids in association with polylysine conjugates used in gene transfer [19,20,22]. Such peptides have demonstrated their efficiency for a gene-transfer system but have not been investigated in depth for ODN delivery.…”
Section: Design and Characterization Of Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are including the E5CA peptide [80,90], dimeric peptide (E5-WYGG)2-KA [101], JTS-1 (GIFEALLESLWELLLEA) [68], GALA (WEAALAEALAEALAEHLAEA-LAEALEALAA) [102,103] and KALA (WEAKL-AKALAKALAKHLAKALAKALKACEA) [104]. All these peptides were believed to have a common property: their α-helix conformation at low pH could disrupt endosome membrane to release more DNA to cytoplasm.…”
Section: Dna Condensation Protection Receptor Targeting and Endosomentioning
confidence: 99%
“…We have reported that the H5WYG peptide (GLFHAIAHFIHGGWHGLIHGWYG) provides membrane permeation at pH 6.8 and increases gene delivery efficiency of DNA/lactosylated polylysine complexes 6. Comparatively, the glutamic counterpart (E5WYG; GLFEAIAEFIEGGWEGLIEGWYG) permeabilises cell membrane at more acidic pH (pH 5.5 and 6.0) 7. In contrast to E5WYG, which adopts an α‐helical structure at pH < 6.0, there is no evidence for H5WYG of a specific conformational structure causing membrane permeation at acidic pH 7–10.…”
Section: Introductionmentioning
confidence: 99%